"CAN('T) YOU SAY HELLO?" CZECH AND ENGLISH POLITENESS STRATEGIES IN INTERCORP - Novakova, Eva (Bohemica Olomucensia, 2022)
The paper discusses the results of a functional contrastive analysis focusing on the most common greetings in Czech and their English equivalents in the parallel corpus InterCorp. It contrasts forms and functions of polite expressions, examines potential cross-linguistic pragmatic shifts, and ponders on usability of corpus data in the research in politeness.
Keywords: politeness; greetings; parallel corpus; pragmatic shifts; contrastive functional analysis